Some Considerations Regarding the Origin and Functions of Parasites among Two Mbya Communities in Misiones, Argentina - Crivos, Marta Alicia (2012)
Fil: Crivos, Marta Alicia. Cátedra de Antropología General. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina